WOMEN EMPOWERMENT AND GENDER EQUALITY IN THE SALE OF BORAN RICE IN LAMONGAN INDONESIA - Yuniar, Dea Hernawati; Riyanto, Edi Dwi; Afdholy, Nadya (EGALITA, 2024)
Abstract Women's empowerment and equality in the economic sector have become widespread due to the successful implementation of the feminist movement. In socialist feminism, the oppression of women in the world of work was rampant, and this has slowly diminished with the empowerment of women in the social and economic sectors. The selling of boran rice by women only in Lamongan, East Java, Indonesia, has a uniqueness because it is one of Lamongan's traditional foods. This research aims to discuss women's empowerment and gender equality in the production and selling practice of boran rice in Lamongan. This research uses descriptive qualitative methods and a phenomenological approach. The data taken in this study is from interviews with boran rice sellers in Lamongan. The results of this research suggest that boran rice sellers do not mind being supporters of the family economy. The women empowerment act is found in the association that houses boran rice sellers in the west of the Lamongan plaza. The gender equality found in the opportunity for women to have a job. This reflects that women and men have their own roles, and their skills are equally useful.. Keywords: Boran Rice; Gender Equality; Women EmpowermentAbstrak Pemberdayaan dan kesetaraan perempuan di sektor ekonomi berkembang pesat karena adanya Gerakan feminisme. Dalam Gerakan feminisme sosialis, penindasan terhadap perempuan di dunia kerja merajalela perlahan-lahan berkurang dengan adanya pemberdayaan perempuan di sektor sosial dan ekonomi. Nasi boran merupakan makanan tradisional Lamongan, Jawa Timur, yang telah menjadi sebuah komoditas. Keunikan dari komoditas ini ialah penjualan nasi boran hanya dilakukan oleh perempuan di Lamongan, Jawa Timur yang tidak dapat ditemukan di daerah lain. Penelitian ini bertujuan untuk mendiskusikan pemberdayaan perempuan dan aspek kesetaraan gender dalam penjualan nasi boran di Lamongan. Penelitian ini menggunakan metode kualitatif deskriptif dan pendekatan fenomenologi. Data yang diambil dalam penelitian ini berasal dari hasil wawancara dengan penjual nasi boran di Lamongan. Hasil wawancara penelitian ini menunjukkan bahwa penjual nasi boran tidak keberatan menjadi salah satu pendukung ekonomi keluarga. Upaya pemberdayaan perempuan ini terdapat pada paguyuban yang menaungi para penjual nasi boran di Lamongan, dan penyerahan tanggung jawab penjualan nasi boran sepenuhnya kepada perempuan. Hal ini mencerminkan bahwa perempuan dan laki-laki memiliki perannya masing-masing, dan keterampilan yang dimiliki masing-masing memiliki manfaat yang sama. Kata Kunci: Nasi Boran; Kesetaraan Gender; Pemberdayaan Perempuan